Contamination levels in and cellular responses of intertidal invertebrates as biomarkers of toxic stress caused by heavy metal contamination in False Bay - Mdzeke, Naomi Patience (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD) -- Stellenbosch University, 2004.